Problematika Ilmu Al-Dilālah Dalam Penerjemahan - Saida Gani (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2020)
A translator is required to have skills in transferring meaning (content) well, so that it is easily accepted and understood by the reader. The process of transferring meaning from the source language, and finding the right equivalent in the target language is not an easy thing. This study aims to analyze the problems of science in translation. The research method is descriptive qualitative with the type of literature review research, where the data sources are obtained from various references related to the study and the problems studied. From the analysis results, the researchers found that the problem in translation is that the translator cannot find or find the equivalent meaning according to the source language and target language. As Mukhtar Umar said that the fundamental problem in the translation process is finding the right equivalent of meaning for a word from the source language into the target language.